Hubungan Kepala Desa, Badan Permusyawaratan Desa serta Lembaga Adat dalam Pelaksanaan Pembangunan Desa (Administratio, 2020)
Village development socially changes social values by discovering the value of technological development in the village of community development that leads to the development of new villages. This of course requires a partnership with the community component. This research aims to explain the relationship between the Village Head, Village Consultative Body and customary institutions in the development of the Village. This research is a field research, namely research on incentives about the background of the present situation and the interaction between social, individuals, groups, institutions and communities in the development of the Village. The study was conducted in Kayeli Subdistrict, Buru Regency. Data in this study were obtained from primary data sources and secondary data, with data collection techniques used through observation, interviews, questionnaires and literature/purposive sampling. The results of the study show the partnership relationship between village heads, village consultative institutions and traditional institutions in Kayeli village demonstrating effectiveness in communication.